Obecność kultury szlacheckiej w Polsce XXI wieku (rekonesans) = The presence of noble culture in 21st century Poland (reconnaissance) - Rogulski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article concerns the presence of noble culture in 21st century Poland, externalized in material and non-material culture. Contemporary Polish society consciously, unconsciously or subconsciously uses the cultural heritage of its noble ancestors, especially in the field of architecture, maintenance of greenery, recipes for culinary and beverages, fashion and the system of values and original customs created by nobilities.
Keywords: kultura szlachecka; dwór polski; system wartości; obyczaje; noble culture; Polish court; value system; custom